Management of X-linked hypophosphatemic rickets: a review - Azar, Mohammed (International Journal of Research in Medical Sciences, 2020)
There are two types of management in X-linked hypophosphatemic rickets (XLH), out of which the main stay of treatment is conventional treatment which includes combination of oral phosphate supplements and active vitamin D (calcitriol or alfacalcidol) after the diagnosis is established. Although, conventional treatment with phosphate supplementation and active vitamin D might improve the rickets and control the renal phosphate excretion but it has significant risk of high calcium excretion in the urine and thereby increases the risk of nephrocalcinosis. The other emerging treatment is burosumab therapy which is human monoclonal IgG1 antibody against fibroblast growth factor 23 (FGF 23) for the treatment of XLH in children ≥1 year of age and in adolescents and is found to be effective in improving rickets without major adverse events. In this review, modalities for XLH treatment over the past and the near future will be discussed along with clinical manifestations and investigations.